2003
DOI: 10.1016/s1525-1578(10)60444-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Patents and Licenses on the Provision of Clinical Genetic Testing Services

Abstract: The growth of patents that include genetic sequences has been accompanied by concern about their impact on the ability of physicians to provide clinical genetic testing services and to perform research. Therefore, we conducted a survey of clinical laboratory directors that perform DNA-based genetic tests to examine potential effects. We performed a telephone survey between July and September in 2001 of all laboratory directors in the United States who were members of the Association for Molecular Pathology or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0
3

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(88 citation statements)
references
References 5 publications
1
84
0
3
Order By: Relevance
“…Here, there are more instances of researchers and firms claiming that the patent owner is asserting exclusivity or license terms that are widely viewed as inappropriate [18,30] [30] find that 25% of labs had abandoned one or more genetic test due to patents, with Myriad's patents among the most frequently mentioned. Such unlicensed lab testing, from the perspective of the patent owner, competes with its commercial activity and hence, it is not surprising to find owners asserting their rights.…”
Section: Reflecting On the Evidencementioning
confidence: 99%
“…Here, there are more instances of researchers and firms claiming that the patent owner is asserting exclusivity or license terms that are widely viewed as inappropriate [18,30] [30] find that 25% of labs had abandoned one or more genetic test due to patents, with Myriad's patents among the most frequently mentioned. Such unlicensed lab testing, from the perspective of the patent owner, competes with its commercial activity and hence, it is not surprising to find owners asserting their rights.…”
Section: Reflecting On the Evidencementioning
confidence: 99%
“…Indeed, he seems to accept conclusions about "the chilling effect of gene patents on the advancement of both genetic research and clinical testing." In support of these kinds of social concerns, Judge Sweet references a handful of studies, including the often-cited survey of laboratory directors by Cho et al, (4 ). That study found that 53% of the respondents agreed that the existence of a patent had led them to decide "not to develop or perform a test/service for clinical or research purposes.…”
Section: The Time Is Right For a Dispassionate Assessmentmentioning
confidence: 99%
“…Although the justification for patents is that they promote innovation, there is growing concern that gene and related patents may be used in ways that could have a significant negative impact on molecular diagnostics in both the clinical and research contexts [51].…”
Section: Impact Of Patents On Clinical Diagnostic Services and Molecumentioning
confidence: 99%
“…One of the reasons why there is more evidence of patent enforcement against clinical molecular diagnostic laboratories in the US than elsewhere might well be because that jurisdiction tends to have a higher ratio of private to public laboratories [51], [56] (recognising that patent holders might also be strategically targeting testing facilities in that jurisdiction because of the higher volume of testing than elsewhere, and hence the greater opportunity for remuneration). Assessment of the impact of patents in the molecular diagnostic landscape requires scrutiny of the changing nature of the landscape, particularly focusing on the increasing commercialisation of this sector.…”
Section: The Legal Landscapementioning
confidence: 99%